Benefits of Kangaroo Mother Care for the “Larger” Low Birth Weight Infant (> 2000g) - Maria UP (SR. Lias) Urakkattil; Suman Rao P N; Pragya Dubey; Swarnarekha Bhat (RGUHS Journal of Nursing Sciences)
Introduction Prematurity and low birth weight LBW are major factors in neonatal mortality and neurodevelopmental disability. Kangaroo Mother Care KMC combining skin-to-skin contact and exclusive breastfeeding is effective in LBW infants. The 2022 WHO recommendations expanded KMC to infants up to 2500 g prompting this study to assess its impact particularly on ldquolargerrdquo LBW infants.Methodology This was an observational study carried out in a South Indian tertiary care hospital included infants 750-2500 g clinically stable for KMC. Physiological parameters were monitored during KMC and conventional care. The study group was stratified by birth weight Group A 750-1499 g Group B 1500-1999 g Group C 2000-2499 g.Results Out of 91 cases the study showed a significant rise in respiratory and heart rates during KMC across all groups. Temperature increased significantly with the largest rise observed in the ldquolargerrdquo LBW infants Group C reducing hypothermia risk by 77. The incidence of mild hypothermia was notably reduced in all groups during KMC with the ldquolargerrdquo LBW infants Group C experiencing the most substantial reduction. The prevalence of mild hypothermia in this group decreased by 39 highlighting the effectiveness of KMC in mitigating hypothermic conditions in larger LBW infants.Discussion The study highlights KMCs effectiveness in preventing hypothermia in larger LBW infants aligning with 2022 WHO guidelines. The temperature rise was more significant in postnatal wards reinforcing KMCs benefits for infants gt2 kg. Conclusion KMC postnatal wards. The study underscores the need for KMC adoption in postnatal care highlighting its benefits for larger LBW infants.